(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The essay «The Meaning of Life, happiness and Success: an existential approach» is devoted to the analysis of fundamental issues of human existence through the prism of existential philosophy. Based on the ideas of Jean-Paul Sartre, Albert Camus, Victor Frankl and other thinkers, the relationship between the meaning of life, the subjective feeling of happiness and socioultural ideas about success is explored. The author examines how personal choice, freedom, and responsibility shape a person’s individual path, and whether it is possible to find genuine satisfaction without resorting to external definitions of meaning and success. The essay invites the reader to reflect on the value of authentic existence in an uncertain and absurd world.